2011
DOI: 10.4049/jimmunol.0903314
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Excessive IL-6 Production In Vivo on the Development and Function of Foxp3+ Regulatory T Cells

Abstract: IL-6 is a proinflammatory cytokine and its overproduction is implicated in a variety of inflammatory disorders. Recent in vitro analyses suggest that IL-6 is a key cytokine that determines the balance between Foxp3+ regulatory T cells (Tregs) and Th17 cells. However, it remains unclear whether excessive IL-6 production in vivo alters the development and function of Foxp3+ Tregs. In this study, we analyzed IL-6 transgenic (Tg) mice in which serum IL-6 levels are constitutively elevated. Interestingly, in IL-6 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 24 publications
5
112
2
2
Order By: Relevance
“…C26-inoculated mice. However, C26 cells are known to produce IL-6 in addition to TGF-β (24), and IL-6 inhibits the induction of Tregs from naïve CD4 + T cells (25). Therefore, there is a possibility that, although the levels of both TGF-β and IL-6 increased in the i.c.…”
Section: Discussionmentioning
confidence: 90%
“…C26-inoculated mice. However, C26 cells are known to produce IL-6 in addition to TGF-β (24), and IL-6 inhibits the induction of Tregs from naïve CD4 + T cells (25). Therefore, there is a possibility that, although the levels of both TGF-β and IL-6 increased in the i.c.…”
Section: Discussionmentioning
confidence: 90%
“…In fact, the role played by IL-6 in the inhibition of Tregs has been debated and it has been suggested that this cytokine preferentially drives the differentiation of Th-0 cells toward Th-17 cells through the blockade of the pathway to Tregs, but does not directly inhibit the proliferation of already differentiated Tregs. 35,36 We were able to retrieve the biopsy taken at the moment of diagnosis of leprosy in five T1R and eight T2R patients, before they developed the reaction episodes. We then compared these biopsies with those taken during the reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, although both IL-10 and IL-6 signal through phosphorylation of STAT3, they have distinct anti-and proinflammatory functions, with IL-6 being critical for Th17 cell induction (8) and unfavorable for iTreg induction (9,10). In this context, the role of IL-10 in iTreg induction remains unanswered.…”
Section: Foxp3mentioning
confidence: 99%